2008
DOI: 10.2214/ajr.07.2653
|View full text |Cite
|
Sign up to set email alerts
|

64-MDCT Coronary Angiography: Phantom Study of Effects of Vascular Attenuation on Detection of Coronary Stenosis

Abstract: Use of higher attenuation leads to a significant underestimation of stenosis in smaller vessels. Lower attenuation leads to slight and clinically acceptable overestimation of stenosis. The optimal vascular attenuation for stenosis detection in coronary 64-MDCT angiography is approximately 350 H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 20 publications
2
57
1
1
Order By: Relevance
“…Many studies have reported the feasibility of coronary CTA for the accurate diagnosis and quantification of these 2 variables in patients with coronary artery disease (CAD), 7-13 but previous experimental and clinical studies have shown that coronary attenuation in coronary CTA affects the assessment of both coronary artery stenosis and plaque. 14- 18 Lower coronary attenuation may decrease the diagnostic accuracy of coronary artery stenosis, whereas higher coronary attenuation may underestimate low-…”
mentioning
confidence: 99%
“…Many studies have reported the feasibility of coronary CTA for the accurate diagnosis and quantification of these 2 variables in patients with coronary artery disease (CAD), 7-13 but previous experimental and clinical studies have shown that coronary attenuation in coronary CTA affects the assessment of both coronary artery stenosis and plaque. 14- 18 Lower coronary attenuation may decrease the diagnostic accuracy of coronary artery stenosis, whereas higher coronary attenuation may underestimate low-…”
mentioning
confidence: 99%
“…Fei et al (2008) reported that the best aortic CT number for cardiac examinations was over 350 HU at 120 kVp for maintaining image quality. Considering the reported data and our clinical experience, our study set the iodine contrast so that to 350 HU at 120 kVp.…”
Section: Discussionmentioning
confidence: 99%
“…We determined that the optimal density for obtaining sharp 3D images of the saphenous, perforator and deep veins in the entire lower extremity with the volume-rendering method was approximately 500 HU (Hounsfield units). 12) We conducted a preliminary study by imaging various dilutions of contrast medium in a test tube, and concluded that a ten-fold dilution was suitable for CT venography.…”
Section: Ct Studymentioning
confidence: 99%